Fucoxanthin-rich fraction from Sargassum fusiformis alleviates particulate matter-induced inflammation in vitro and in vivo. (2021) - Dai, Yu-Lin; Jiang, Yun-Fei; Lu, Yu-An; Yu, Jiang-Bo; Kang, Min-Cheol; Jeon, You-Jin
Abstract: Particulate matter (PM) contributes to air pollution and primarily originates from unregulated industrial emissions and seasonal natural dust emissions. Fucoxanthin (Fx) is a marine natural pigment from brown macroalgae that has been shown to have various beneficial effects on health. However, the effects of Fx on PM-induced toxicities in cells and animals have not been assessed. In this study, we investigated the anti-inﬂammatory potential of the Fx-rich fraction (FxRF) of Sargassum fusiformis against PM-mediated inﬂammatory responses. The FxRF composition was analyzed by rapid-resolution liquid chromatography mass spectrometry. Fx and other main pigments were identified. FxRF attenuated the production of inﬂammatory components, including prostaglandin E2 (PGE2 ), cyclooxygenase-2, interleukin (IL)-1β, and IL-6 from PM-exposed HaCaT keratinocytes. PM exposure also reduced the levels of nitric oxide (NO), tumor necrosis factor-α, inducible nitric oxide synthase (iNOS), and PGE2 in PM-exposed RAW264.7 macrophages. Additionally, the culture medium from PM-exposed HaCaT cells induced upregulation of NO, iNOS, PGE2, and pro-inﬂammatory cytokines in RAW264.7 macrophages. FxRF also significantly decreased the expression levels of factors involved in inﬂammatory responses, such as NO, reactive oxygen species, and cell death, in PM-exposed zebrafish embryos. These results demonstrated the potential protective effects of FxRF against PM-induced inflammation both in vitro and in a zebrafish model.